2014
DOI: 10.1016/j.msea.2014.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic properties of Al–Mg–Sc–Zr friction-stir welds

Abstract: a b s t r a c tIn this work, the effect of friction-stir welding (FSW) on the microstructure and cryogenic properties of an Al-Mg-Sc-Zr alloy was studied. The produced friction-stir joints demonstrated both excellent static and dynamic mechanical properties at cryogenic temperatures. The joint efficiency for the yield strength during transverse tensile tests was in the range of 95-100%, whereas the impacts fracture toughness in the stir zone was found to be superior compared with that in the base material. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
2
19
0
4
Order By: Relevance
“…Therefore, the conventional technologies are obviously not appropriate for this processing route. In contrast, the friction-stir welding (FSW) technique enables preservation of the fine-grained structure [10][11][12][13][14] and avoids dissolution of the unique Al 3 Sc dispersoids [7][8][9][14][15][16][17][18][19][20] in the weld zone, making FSW particularly promising for use in the joining of UFG Al-Mg-Sc alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the conventional technologies are obviously not appropriate for this processing route. In contrast, the friction-stir welding (FSW) technique enables preservation of the fine-grained structure [10][11][12][13][14] and avoids dissolution of the unique Al 3 Sc dispersoids [7][8][9][14][15][16][17][18][19][20] in the weld zone, making FSW particularly promising for use in the joining of UFG Al-Mg-Sc alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conventional technologies are obviously not appropriate for this processing route. In contrast, the friction-stir welding (FSW) technique enables preservation of the fine-grained structure [10][11][12][13][14] and avoids dissolution of the unique Al 3 Sc dispersoids [7][8][9][14][15][16][17][18][19][20] in the weld zone, making FSW particularly promising for use in the joining of UFG Al-Mg-Sc alloys.Recent studies have demonstrated that friction-stir processed Al-Mg-Sc alloys exhibit excellent superplastic properties [21][22][23][24][25][26][27][28]. Specifically, the maximum elongation-to-failure value may sometimes exceed 2000% [21, 24, 27].…”
mentioning
confidence: 99%
“…[1,2] At subzero temperatures, these mechanical characteristics increase linearly with decreasing temperature; [1,[3][4][5][6] this is in contrast to conventional steel materials, which typically lose most of their ductility and toughness below the ductile-brittle transition (DBT) temperature. [1,2] At subzero temperatures, these mechanical characteristics increase linearly with decreasing temperature; [1,[3][4][5][6] this is in contrast to conventional steel materials, which typically lose most of their ductility and toughness below the ductile-brittle transition (DBT) temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, in high-strength steels at room temperature, the grain boundary strengthening by refining the grain size to 1 mm or less results in low toughness and low tensile ductility due to reducing the work hardening capacity, although fracture occurs in a ductile manner. [4] Note that the effect of grain size on strength and toughness of steels has been well-examined, [7,8] while a limited number of studies has addressed aluminum alloys. [4] Note that the effect of grain size on strength and toughness of steels has been well-examined, [7,8] while a limited number of studies has addressed aluminum alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation